2020
DOI: 10.1002/jhbp.716
|View full text |Cite
|
Sign up to set email alerts
|

Chyle leakage after robotic and open pancreaticoduodenectomy

Abstract: Background: Chyle leakage is a well-known but poorly characterized complication after pancreaticoduodenectomy (PD). No study examined the chyle leakage after robotic PD (RPD). Methods: Data regarding chyle leakage were prospectively collected and analyzed from patients undergoing RPD or open PD (OPD). Results: The study included 118 RPD and 165 OPD. Overall chyle leakage rate was 12.0%, with 13.6% for RPD and 10.9% for OPD. Chyle leakage was eventually resolved in all patients through conservative treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…However, the chyle leakage rate was high, with 25.0% overall and 19.1% and 30.5% in the early and late groups, respectively. The association between level III mesopancreas dissections and chyle leakage was described in our previous study 8,27 . As expected, the more level III mesopancreas dissections, the greater the chyle leakage, especially in the late group, as shown in this RPD series.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the chyle leakage rate was high, with 25.0% overall and 19.1% and 30.5% in the early and late groups, respectively. The association between level III mesopancreas dissections and chyle leakage was described in our previous study 8,27 . As expected, the more level III mesopancreas dissections, the greater the chyle leakage, especially in the late group, as shown in this RPD series.…”
Section: Discussionsupporting
confidence: 84%
“…The association between level III mesopancreas dissections and chyle leakage was described in our previous study. 8,27 As expected, the more level III mesopancreas dissections, the greater the chyle leakage, especially in the late group, as shown in this RPD series. After the learning curve was overcome as shown in our previous study, 28 the present study demonstrated that RPD is feasible and safe over time.…”
Section: -Year Survival (%) P-valuesupporting
confidence: 78%
“…In the present study, the duration median was 8, 3, or 7 days in hepatobiliary surgery, gastrointestinal surgery, and urological surgery. For gynecological surgery patients with chylous leakage cured by TPN alone, the median was 15 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) days (60). The median for days of drainage was 3 (1-21) days (3 cases discharged with a drainage tube on day 1 of intervention and 1 on day 2) in the present study under a similar condition.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective study specifically investigating CL in open (n = 118) versus robot PD (n = 165), found no effect of the surgical approach on CL (10.9% vs 13.6%, P = 0.449). 28 In the 4 randomized trials on laparoscopic versus open PD, only the multicenter randomized LEOPARD-2 trial reported on the incidence of CL. [29][30][31][32] A nonsignificant increase in CL after laparoscopic as compared with open PD (n = 2/50 [4%] vs n = 7/49 [14%], P = 0.09) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is conflicting on this point. A single-center retrospective study specifically investigating CL in open (n=118) versus robot PD (n=165), found no effect of the surgical approach on CL (10.9% vs 13.6%, P =0.449) 28. In the 4 randomized trials on laparoscopic versus open PD, only the multicenter randomized LEOPARD-2 trial reported on the incidence of CL 29–32.…”
Section: Discussionmentioning
confidence: 99%